An exploratory study of punctuation in bilingual children's texts - Clavijo Olarte, Amparo; Freeman, Ann; García Obregon, Andrea (Colombian Applied Linguistics Journal, 2004)
This article describes first and second grade children's writing and focuses on the uses of punctuation as they develop awareness of the orthographic features of texts. This exploratory study was carried out with a group of first and second grade bilingual children in a school in Tucson, Arizona. Our research project focused on observing the process bilingual children followed when writing the story of Caperucita Roja to analyse thje content of their texts in the different episodes of their stories and the use of punctuation around dialogue and narratives. The findings show that the mejority of children were aware of the use of punctuation marks in their writings. We found a direct relation between puntuation and the use of dialogue (indirect speech) in children texts. Children used additional (sintactic and lexical) forms in their texts that demostrate that they know the use of direct speech. children's texts exhibited very little use of punctuation in their narratives; they only used period and capital letters.